2015
DOI: 10.1007/s12032-015-0547-5
|View full text |Cite
|
Sign up to set email alerts
|

C23 protein meditates bone morphogenetic protein-2-mediated EMT via up-regulation of Erk1/2 and Akt in gastric cancer

Abstract: In our previous study, the epithelial-to-mesenchymal transition (EMT) has been identified to be involved in gastric cancer progression. Notably, nuclear protein C23 and bone morphogenetic protein-2 (BMP2) have been linked into EMT. However, the specific mechanisms underlying BMP2 pathway-mediated EMT are not still unraveled. In this study, we adopted immunohistochemistry and immunoblotting to determine the expression of C23 and BMP2 receptor II (BMPR-II) in 90 gastric cancer samples and cell lines. Subsequentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Conversely, over expression of CHRDL1 induced Akt dephosphorylation (Figure 3B). Yang Y et al reported that Akt and Erk can also be phosphorylated by BMPR II [27]. Therefore, we also measured Erk in our experiment.…”
Section: Resultsmentioning
confidence: 77%
“…Conversely, over expression of CHRDL1 induced Akt dephosphorylation (Figure 3B). Yang Y et al reported that Akt and Erk can also be phosphorylated by BMPR II [27]. Therefore, we also measured Erk in our experiment.…”
Section: Resultsmentioning
confidence: 77%
“…These observations indicated a role of this cell type to regulate oncogenic potential in epithelial cells using a fibroblast-specific TGF-Ī² receptor 2 knockout model (Tgfbr2fspKO). Alternatively, TGF-Ī² ligand BMP-2 induces invasion and cancer stem features via STAT3 activation during colon cancer [ 35 ], and ERK1/2 and AKT during gastric cancer [ 57 , 58 , 59 ]. Tissue scarring depicted by fibrosis, followed by the administration of tumor necrosis factor alpha (TNF-Ī±), leads to mesenchymal marker expression [ 60 ].…”
Section: Emt Classificationsmentioning
confidence: 99%
“…For instance, transfecting cells with nucleolin-targeted small interfering RNA could result in the inhibition of the EMT phenotypes. 22 Yang et al 23 showed that si-nucleolin treatment attenuated the BMP2-induced expression of p-Erk1/2, p-Akt, vimentin, N-cadherin, and MMP2, leading to decreased migration and invasion of gastric cancer cells. Nucleolin also modulates matrix metalloproteinases (MMPs).…”
Section: Nucleolin In Cancer Infiltration and Metastasismentioning
confidence: 99%